Adaptations of early development to local spawning temperature in anadromous populations of pike (Esox lucius) - Johanna Sunde; Per Larsson; Anders Forsman (BMC Evolutionary Biology, 2019)
Abstract Background In the wake of climate change many environments will be exposed to increased and more variable temperatures. Knowledge about how species and populations respond to altered temperature regimes is therefore important to improve projections of how ecosystems will be affected by global warming, and to aid management. We conducted a common garden, split-brood temperature gradient (4.5 °C, 9.7 °C and 12.3 °C) experiment to study the effects of temperature in two populations (10 families from each population) of anadromous pike (Esox lucius) that normally experience different temperatures during spawning. Four offspring performance measures (hatching success, day degrees until hatching, fry survival, and fry body length) were compared between populations and among families. Results Temperature affected all performance measures in a population-specific manner. Low temperature had a positive effect on the Harfjärden population and a negative effect on the Lervik population. Further, the effects of temperature differed among families within populations. Conclusions The population-specific responses to temperature indicate genetic differentiation in developmental plasticity between populations, and may reflect an adaptation to low temperature during early fry development in Harfjärden, where the stream leading up to the wetland dries out relatively early in the spring, forcing individuals to spawn early. The family-specific responses to temperature treatment indicate presence of genetic variation for developmental plasticity (G x E) within both populations. Protecting between- and within-population genetic variation for developmental plasticity and high temperature-related adaptive potential of early life history traits will be key to long-term viability and persistence in the face of continued climate change.